PEMETAAN SEBARAN KANDUNGAN TINGKAT KEASAMAAN (pH) AIR SUNGAI MAHAP KABUPATEN SEKADAU - Ika Muthya Anggraini; Hezliana Syahwanti (Fakultas Teknik Universitas Panca Bhakti, 2022)
Mahap River water pollution comes from oil palm and rubber plantation areas in the upper reaches of the river. In addition, agricultural activities in the homes of local residents also contributed to the decline in water quality. Mahap River is a source of clean water for local residents. Agricultural waste can lower the pH of the water. This decrease in pH value is acidic and corrosive, causing metal toxicity and inhibiting the nitrification process. Based on this, it is necessary to map the level of acidity (pH) of the Mahap River so that the safety of the water can be known specifically. The results of this study show that the pH value becomes more acidic when the direction of the river goes to a lower place, which is closer to Riyam Engkayak. This is because the area above the riyam is a residential area for residents. This is because the area above the riyam is a residential area where waste from residents' activities both come from households and from residents' agricultural activities.